Hyperthermia, but not muscle water deficit, increases glycogen use during intense exercise - Fernandez-Elias, V. E.; Hamouti, N.; Ortega, J. F.; Mora-Rodriguez, R. (Scandinavian Journal of Medicine & Science in Sports, 2015)
We determined if dehydration alone or in combination with hyperthermia accelerates muscle glycogen use during intense exercise. Seven endurance-trained cyclists (VO2max = 54.4 ± 1.05 mL/kg/min) dehydrated 4.6% of body mass (BM) during exercise in the heat (150 min at 33 ± 1 °C, 25 ± 2% humidity). During recovery (4 h), subjects remained dehydrated (HYPO trial) or recovered all fluid losses (REH trials). Finally, subjects exercised intensely (75% VO2max) for 40 min in a neutral (25 ± 1 °C; HYPO and REH trials) or in a hot environment (36 ± 1 °C; REHHOT). Before the final exercise bout vastus lateralis glycogen concentration was similar in all three trials (434 ± 57 mmol/kg of dry muscle (dm)) but muscle water content was lower in the HYPO (357 ± 14 mL/100 g dm) than in REH trials (389 ± 25 and 386 ± 25 mL/100 g dm; P < 0.05). After 40 min of intense exercise, intestinal temperature was similar between the HYPO and REHHOT trials (39.2 ± 0.5 and 39.2 ± 0.4 °C, respectively) and glycogen use was similar (172 ± 86 and 185 ± 97 mmol/kg dm, respectively) despite large differences in muscle water content. In contrast, during REH, intestinal temperature (38.5 ± 0.4 °C) and glycogen use (117 ± 52 mmol/kg dm) were significantly lower than during HYPO and REHHOT. Our data suggest that hyperthermia stimulates glycogen use during intense exercise while muscle water deficit has a minor role.